(untitled) (Baghdad Science Journal, 2015)
The aim of this research to show the role of some enzymes in pathological mechanism of rheumatoid arthritis (RA) disease. Sixty patients with RA and matched number of apparently healthy volunteers were included in the study. Spectrophotometric methods were used to determine Peroxy nitrite (ONOO), Nitric oxide (NO), Nitric oxide synthase activity (NOS) cycloxygenase-2 activity (COX-2), glutathione peroxidase (GPX) activity and superoxide dismutase (SOD) activity in serum of both groups. Colorimetric assay kits were used to determine Iron. Rheumatoid factor (RF) was determined using Imuno-Latex kit. ONOO, NO levels, and NOS activity were significantly higher in the patients compared to the control group. Conversely, Iron level, SOD activity and GPX activity were significantly lower in the patients compared to the control. In patients group, RF has significant positive correlation with COX-2, NOS activity and NO level while; it has significant negative correlation with Iron level. ONOO level has significant positive correlation with NO level, NOS activity and COX-2 activity while has significant negative correlation with Iron and SOD activity. NOS activity and NO level have significant positive correlation with COX-2 activity while, they have negative correlation with Iron. Iron has significant negative correlation with COX-2 activity. In control group, COX-2 has significant positive correlation with NOS activity and ONOO level. GPX has significant positive correlation with SOD and Iron. In conclusion: disorder activity of COX-2, NOS, SOD and GPX enzymes play important role in the pathological mechanism of rheumatoid arthritis and they linked with a decreased level of serum iron